Developing and validating a multidimensional tourist engagement scale (TES). Issue 7 (11th June 2019) - Huang, Shuyue; Choi, Hwan-Suk Chris
ABSTRACT: Customer engagement (CE) narrows the focus of experience to the interactive, value co-creative process between customers and company. Despite a few attempts measuring online engagement, we found no studies on fully operationalized engagement in the tourism destination. Considering the existing CE scales might not fully capture the scope of value co-creation process and its context-dependent nature, we proposed to develop a tourist engagement scale (TES) which incorporates more actors in value co-creation at the destination. Following the procedures of item generation, scale purification, and scale validation, we identified a 16-item, four-dimensional, second-order model of TES: social interaction, interaction with employees, relatedness, and activity-related tourist engagement (including immersed involvement and novelty-seeking). It provides various uses to DMOs and service providers, e.g. an assessment tool for tourist experience, a market segment tool, and a predictor to tourists' behavioral intention. We contribute to the literature of tourist experience, value co-creation, and engagement study.